Ascorbic acid improves impaired venous and arterial endotheliumdependent dilation in smokers - SOUSA Márcio Gonçalves de; YUGAR-TOLEDO Juan Carlos; RUBIRA Marcelo; FERREIRA-MELO Sílvia Elaine; PLENTZ Rodrigo; BARBIERI Deise; CONSOLIM-COLOMBO Fernanda; IRIGOYEN Maria Cláudia; MORENO Jr Heitor (Acta Pharmacologica Sinica, 2016)
Aim: To compare the acute effects of ascorbic acid on vasodilation of veins and arteries in vivo. Methods: Twenty-six healthy non-smokers and 23 healthy moderate smokers were recruited in this study. The dorsal hand vein compliance technique and flow-mediated dilation were used. Dose-response curves to bradykinin and sodium nitroprusside were constructed to test the endothelium-dependent and -independent relaxation before and after acute infusion of ascorbic acid. Results: Smokers had an impaired venodilation with bradykinin compared with non-smokers (68.3%±13.2% vs 93.7%±20.1%, respectively; P